2019
DOI: 10.3390/polym11071216
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Assessment of Commercial Photoluminescent Pigments Printed on Cotton Fabric

Abstract: The presented study focuses on photoluminescent pigments applied on cotton fabric by a screen-printed procedure using polydimethylsiloxane (PDMS) as a binder. Microscopic data depicts irregular shapes and relatively wide size distribution (3–80 µm) of pigments. Regarding composition, the Energy-Dispersive X-ray (EDX) and Fourier Transform Infrared (FTIR) spectroscopy data complement findings suggesting the presence of Eu-doped strontium aluminate in the yellow-green, calcium aluminate in the violet pigment, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…[1][2][3][4][5][6] The industry making technical textiles holds great potential significance in the marketing of nano-based merchandise, particularly antimicrobial as well as other promising medical and protective technical textiles. [7][8][9][10][11] These nano-based smart textile materials can be promptly initiated with the implementation of metal-based nanoparticles (NPs) during the finishing processing of different fibrous materials. Modern studies have demonstrated that the great potential of metal oxide NPs can be effectively employed to manufacture highly added-value textile materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The industry making technical textiles holds great potential significance in the marketing of nano-based merchandise, particularly antimicrobial as well as other promising medical and protective technical textiles. [7][8][9][10][11] These nano-based smart textile materials can be promptly initiated with the implementation of metal-based nanoparticles (NPs) during the finishing processing of different fibrous materials. Modern studies have demonstrated that the great potential of metal oxide NPs can be effectively employed to manufacture highly added-value textile materials.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements were performed within a spectral range of 400–700 nm wavelengths using a two-ray spectrophotometer Spectraflash SF600 Plus (Datacolor, Trenton, NJ, USA) at standard illuminant D65 (LAV/Spec. Incl., d/8, D65/10°), from which the CIE color values were calculated using the Datacolor Match Textile 2.6.3.19R software (Datacolor, Trenton, NJ, USA) [ 31 , 32 ]. A Xenon halogen lamp was used as the light source.…”
Section: Methodsmentioning
confidence: 99%
“…Gorgieva et al prepared a PDMS coating containing commercial fluorescent dyes and printed it on cotton fabrics to obtain luminous textile prints with excellent washing and abrasion resistance through a facile and effective screen-printing method. [93]…”
Section: Coatingsmentioning
confidence: 99%